Expression of Programmed Death-Ligand 1 by Human Colonic CD90+ Stromal Cells Differs Between Ulcerative Colitis and Crohn’s Disease and Determines Their Capacity to Suppress Th1 Cells - Beswick, Ellen J.; Grim, Carl; Singh, Abinav; Aguirre, Jose E.; Tafoya, Marissa; Qiu, Suimin; Rogler, Gerhard; McKee, Rohini; Samedi, Von; Ma, Thomas Y.; Reyes, Victor E.; Powell, Don W.; et al. (Frontiers in Immunology, 2018)
Background and Aims: The role of PD-1 and its ligands in the dysregulation of T helper (Th) immune responses observed in the inflammatory bowel disease (IBD) is unclear. Recently, a novel concept emerged that CD90+ colonic (myo)fibroblasts (CMFs), also known as stromal cells, act as immunosuppressors, and are among the key regulators of acute and chronic inflammation. The objective of this study was to determine if the level of the PD-1 ligands is changed in the IBD inflamed colonic mucosa and to test the hypothesis that changes in IBD-CMF mediated PD-1 ligand–linked immunosuppression is a mechanism promoting the dysregulation of Th1 cell responses. Methods: Tissues and cells derived from Crohn’s disease (CD), ulcerative colitis (UC) and healthy individuals (N) were studied in situ, ex vivo and in culture. Results: A significant increase in PD-L1 was observed in the inflamed UC colonic mucosa when compared to the non-inflamed matched tissue samples, CD and healthy controls. UC-CMFs were among the major populations in the colonic mucosa contributing to the enhanced PD-L1 expression. In contrast, PD-L1 expression was decreased in CD-CMFs. When compared to CD-CMFs and N-CMFs, UC-CMFs demonstrated stronger suppression of IL-2, Th1 transcriptional factor Tbet and IFN-γ expression by CD3/CD28- activated CD4+ T cells and this process was PD-L1 dependent. Similar observations were made when differentiated Th1 cells were co-cultured with UC-CMFs. In contrast, CD-CMFs showed reduced capacity to suppress Th1 cell activity and addition of recombinant PD-L1 Fc to CD-CMF:T cell co-cultures partially restored the suppression of the Th1 type responses. Conclusions: We present evidence showing that increased PD-L1 expression suppresses Th1 cell activity in UC. In contrast, loss of PD-L1 expression observed in CD contributes to the persistence of the Th1 inflammatory milieu in CD. Our data suggest that dysregulation of the Th1 responses in the inflamed colonic mucosa of IBD patients is promoted by the alterations in PD-L1 expression in the mucosal mesenchymal stromal cell compartment.